PENGEMBAGAN LEMBAR KERJA SISWA BERBASIS KONTEKSTUAL TEACHING AND LEARNING UNTUK TUNARUNGU - Muhammad Iqbal; Bambang Sri Anggoro; Rosida Rakhmawati (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2020)
The purpose of this study is to develop worksheets based on contextual teaching and learning for the deaf. The method that will be used is the method of research and development. The development procedure used is the procedure of borg and gall. The technique of data collection used is random class techniques. The sample used is the SMALB Dharma bhakti dharma pertiwi students. The data collection techniques used were interviews, observations and questionnaires. The data analysis technique used is descriptive qualitative and descriptive quantitative. The main results of this research and development are LKS based on contextual teaching and learning for the deaf. Based on the results of the validation to the material experts and LKS media experts developed, the criteria were very feasible to use. Judging from the LKS field trials that were developed, obtaining very interesting criteria to be used in mathematics learning. Based on this matter, it is concluded that mathematics student books for students with inquiry approaches for students developed for the deaf are very feasible and very interesting to be used in mathematics learning for deaf students. Tujuan penelitian ini adalah mengembangkan LKS berbasis kontekstual teaching and learning untuk tunarungu. Metode yang akan digunakan adalah metode penelitian dan pengembangan. Prosedur pengembangan yang digunakan adalah prosedur dari borg and gall. Tehnik pengumpulan data yang digunakan adalah tehnik acak kelas. Sampel yang digunakan adalah siswa SMALB Dharma bhakti dharma pertiwi. Tehnik pengembilan data yang digunakan adalah wawancara, observasi dan angket. tehnik analisis data yang digunakan adalah deskristif kualitatif dan deskristif kuantitatif. Hasil utama dari penelitian dan pengembangan ini adalah LKS berbasis kontekstual teaching and learning untuk tunarungu. Berdasarkan hasil validasi kepada ahli materi dan ahli media LKS yang dikembangkan memperoleh kriteria sangat layak digunakan. Ditinjau dari uji coba lapangan LKS yang dikembankan memperoleh kriteria sangat menarik untuk digunakan dalam pembeljaran matematika. Berdasarkan hal ini daopat disimpulkan bahwa buku siswa matematika untuk siswa dengan pendekatan inkuiri untuk siswa yang dikembangkan untuk tunarungu sangat layak dan sangat menarik untuk digunakan dalam pemebalajaran matematika siswa tunarungu.